(3QSGdI aj GdCMGOjK GdbOSjIs - (3eLghds
(3ChdgG (B:s
(3gPG MOjK bOSj HSe Gddg GdQMef GdQMje ShQI GdChd bGd Gddg JHGQc hJYGdi YLHJ def Cjbf HGdehJ cja jaQM hYLHJ def Cjbf HGdMSGH cja jLeY GdeGds
(3BNQgG (B:s
(3CehQ XGgQGJ ef ZjQ Naj UGOfj GdUjGO jG hdO GdMQGe jG ehdGj jG ehdGjs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdMOjK hGdeUWdMs